A novel TSC2 c.4511 T > C missense variant associated with tuberous sclerosis complex - Shunzhi He; Na Lv; Hongchu Bao; Xiong Wang; Jing Li (BMC, 2020)
Abstract Background Tuberous sclerosis complex (TSC) is an autosomal-dominant hereditary disease characterized by hamartomas of multiple organ systems, including the brain, skin, heart, kidney and lung. Genetically, TSC is caused by pathogenic variants in the TSC1 or TSC2 gene. Case presentation We reported a sporadic case of a 32-year-old Han Chinese male diagnosed with TSC, whose spouse had a history of two spontaneous miscarriages and an induced abortion of a 30-week fetus identified with cardiac rhabdomyoma by ultrasound. A novel heterozygous missense variant in the TSC2 gene (Exon35:c.4511 T > C:p.L1504P) was identified in the male patient and the aborted fetus by next-generation sequencing, but not in his wife or both his parents. According to the ACMG/AMP criteria, this variant was classified as a "likely pathogenic" variant. Conclusion The novel TSC2:c.4511 T > C variant identified was highly likely associated with TSC and could potentially lead to adverse reproductive outcomes. IVF-ET and pre-implantation genetic diagnosis for TSC are recommended for this patient in the future to prevent fetal TSC.